Analysis of the Behavior of Accounts Receivables of The Nagari Taeh Bukik Community, Payakumbuh District, Fifty District - Grawenita, Widya; Parsaulian, Baginda (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2023)
The research that the authors conducted was motivated by the behavior of the Nagari Taeh Bukik community in paying debts to conventional financial institutions and other sources. The purpose of the research that the authors conducted was to determine the behavior of the debts and receivables of the Nagari Taeh Bukik community. The research method that the writer uses is field research with a qualitative descriptive approach. Sources of date from the research that the authors did, namely primary data and secondary data. Data collection techniques are observations, interviews and documentation. The date analysis technique used by the author is data prediction, data presentation, and decision making. The results of the research that the officials conducted were: (1) people have various forms of behavior in making debt decisions. The high needs of life make people choose debt to meet their needs. Not only to meet their daily needs they are in debt but, even for the fulfillment of their desires they are also in debt. (2) people's behavior in making debt decisions is influenced by two factors: internal factors (age, work, economic situation, lifestyle, personality, motivation, perception, and learning process) and external factors (culture, education, religion, and family).